2009
DOI: 10.1128/jvi.01890-08
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Neuroinvasion: Identification of Infected Cells

Abstract: Hepatitis C virus (HCV) infection often is associated with cognitive dysfunction and depression. HCV sequences and replicative forms were detected in autopsy brain tissue and cerebrospinal fluid from infected patients, suggesting direct neuroinvasion. However, the phenotype of cells harboring HCV in brain remains unclear. We studied autopsy brain tissue from 12 HCV-infected patients, 6 of whom were coinfected with human immunodeficiency virus. Cryostat sections of frontal cortex and subcortical white matter we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(160 citation statements)
references
References 45 publications
(42 reference statements)
6
144
0
10
Order By: Relevance
“…Based on the relatively low HCV RNA content in brain to the liver, detection of HCV antigen in the brain is extremely challenging, and existing imaging methodologies are not sensitive enough to detect the cells of CNS that are infected by the virus [29] . Prior studies have shown the presence of HCV RNA in microglia and astrocytes that were also isolated by laser capture microdissection [36,37] . Another study has shown that two independently derived brain endothelial cell lines (hCMEC/D3 and HBMEC) facilitate the entry and replication of the virus.…”
Section: Replication Of Hcv In Brainmentioning
confidence: 99%
“…Based on the relatively low HCV RNA content in brain to the liver, detection of HCV antigen in the brain is extremely challenging, and existing imaging methodologies are not sensitive enough to detect the cells of CNS that are infected by the virus [29] . Prior studies have shown the presence of HCV RNA in microglia and astrocytes that were also isolated by laser capture microdissection [36,37] . Another study has shown that two independently derived brain endothelial cell lines (hCMEC/D3 and HBMEC) facilitate the entry and replication of the virus.…”
Section: Replication Of Hcv In Brainmentioning
confidence: 99%
“…Furthermore, fatigue or depression is found in many patients with chronic HCV infection, with incidences of about 50% and 35%, respectively [173][174][175] . These neurocognitive dysfunctions have been characterized epidemiologically or pathophysiologically in chronic HCV infection [166,167,176] , and may be explained by the neuroinvasion of HCV, because HCV has been reported to be found in monocytes/microglia of the central nervous system [176,177] . However, antiviral treatment with interferon, particularly interferon-α, is known to exacerbate depression [178] .…”
Section: Polyneuropathy and Neurocognitive Dysfunctionmentioning
confidence: 99%
“…Mixed cryoglobulinemia is the most-well-characterized HCV-associated disease and is curable by viral clearance through antiviral therapies (6). Although replication of HCV RNA in peripheral blood mononuclear cells (PBMCs) and neuronal cells at a low level was suggested (64), the biological significance of the extrahepatic replication of HCV, particularly in the development of EHMs, is not well understood.…”
mentioning
confidence: 99%